Evaluation of the Scout Extracurricular Program to Improve the Character of Elementary School Students - Ervitasari, Aning; Iriani, Ade (Indonesian Values and Character Education Journal, 2022)
The low character possessed by students causes a decline in ethics and morals among students. So efforts are needed to be able to improve the character possessed by students. The purpose of this study was to evaluate the achievement of the goals of the cub scout extracurricular program. This research is a qualitative descriptive study, and its evaluation uses the goal-free evaluation model. The research subjects were school principals, cub masters, scout trainers, and 58 extracurricular participants. Observations, interviews, and documentation studies are the data collection techniques used in this study. Data analysis techniques were carried out in four stages, starting from 1) data collection, 2) data reduction, 3) data presentation, and 4) conclusion. The data validity in this study used technique and source triangulation. The results showed that the scout extracurricular improved students' character because character education was implemented in the content. Still, the purpose of the scout extracurricular program had not been achieved 100%. So it is hoped that these extracurricular activities will be carried out more intensively to have a positive impact, especially in shaping and developing student character.